Developing a method for evaluating global university rankings - Elizabeth Gadd; Richard Holmes; Justin Shearer (2021)
Describes a method to provide an independent, community-sourced set of best practice criteria with which to assess global university rankings and to identify the extent to which a sample of six rankings, Academic Ranking of World Universities (ARWU), CWTS Leiden, QS World University Rankings (QS WUR), Times Higher Education World University Rankings (THE WUR), U-Multirank, and US News & World Report Best Global Universities, met those criteria. The criteria fell into four categories: good governance, transparency, measure what matters, and rigour. The relative strengths and weaknesses of each ranking were compared. Overall, the rankings assessed fell short of all criteria, with greatest strengths in the area of transparency and greatest weaknesses in the area of measuring what matters to the communities they were ranking. The ranking that most closely met the criteria was CWTS Leiden. Scoring poorly across all the criteria were the THE WUR and US News rankings. Suggestions for developing the ranker rating method are described.